Synergistic Performance 0f Islamic Religious Education Educators with Counseling Guidance Educator in Overcoming Learner Anxiety in SMAN 2 Sungai Limau - Ramadhani, Ilham (Program Pascasarjana UMSB, 2024)
Study This in the background back by many participant the learner does it violation system orderly as well as do mischief inside environment school . such as : Skipping class , getting dressed No polite / neat , fighting , dating , disrupting the learning process . This matter naturally very disrupt the learning process at school. Objective Research 1)Forms mischief participant education carried out in the environment school in violate system orderly school at SMAN 2 Sungai Limau .2)Factors that become source reason mischief participant studied at SMAN 2 Sungai Limau .3) Shape performance carried out educator Islamic Religious Education and educator Guidance Counseling in overcome mischief participant studied at SMAN 2 Sungai Limau. Study This is study field ( field research ) which is of a nature qualitative with use method descriptive , that is with illustrate object study as exist . Primary research data source covers participant educate and secondary data covers educator Islamic Religious Education , Educator Guidance Counseling at SMAN 2 Sungai Limau . Procedure deep data collection study This is interview in-depth,observation And documentation.Technique Data validity includes: Credibility , transferability, dependability And confirmability. Results study This showing that : 1) Form mischief participant education carried out in the environment SMAN 2 Sungai Limau in violate system orderly school that is like withdraw, be late , oppose teacher,wandering outside class ,smoking and others.2) Shape performance carried out educator Islamic religious education and educator guidance counseling at SMAN 2 Sungai Limau in overcome mischief participant educate that is with do activity counseling Islamic, observing Act in demand participant educate ,approach personal And give doubt in accordance existing rules made by party school . 3) Factors that become source reason mischief participant studied at SMAN 2 Sungai Limau is circumstances family,circumstances school , circumstances environment, technology And Friend very similar influence participant educate .No only That Also There is originating factors from in self participant educate That Alone . Such as : intelligence , type gender , age , change biological And psychological on self somebody And control weak self .Keyword : Educator Performance; Islamic Religious Education; Guidance Counseling; Student Delinquency